Establishment of 50-120 kV Pulsed X-ray Reference Radiation Field and Dose Rate Measurement - HAO Guanghui, ZHANG Xiaole, XU Zhui, LI Dehong, HUANG Jianwei, CHENG Jianbo, WAN Linjian (Journal of Isotopes, 2024)
In order to meet the needs of accurate traceability of dose monitoring instruments in domestic medical, security inspection and other pulse radiation places, a 50-120 kV millisecond pulse X-ray reference radiation field that meets the requirements of norms and standards was established, based on the gate control technology, and its pulse width can be adjustable in the range of 1-6 300 ms. The pulse X-ray reference waveform was established by studying and testing the tube voltage stability, dose linearity, repeatability, pulse waveform and other key parameters of the radiation field, and the pulse dose rate was measured using a cylindrical ionization chamber with a sensitive volume of 30 cm3, and obtained the following research results: when the tube voltage was preset to 60 kV, the relative deviation of the intervened and non-intervened measuring tube voltage did not exceed ±1.5%; the minimum pulse width of the reference waveform pulse output was 20 ms, and a 95% uniform radiation field with a diameter of about 5.5 cm could be generated at 1 m. Moreover, the dose rate range of N series and RQR series radiation quality was extended to 0.002-10 mGy/s and 0.03-250 mGy/s, respectively, which can be used for the metrological traceability of protective instruments.